Evaluasi Pengajaran Guru Bahasa Arab di MAN III Rawasari, Jakarta Pusat - Siti Jubaidah (Universitas Negeri Jakarta, 2015)
Teacher’s self evaluation is a way to guide teachers in identifying strengths and weaknesses in learning. Improving teacher’s professionalism started by recognizing and realizing the weaknesses in learning, and by a willingness to enhance self competence. This article is a result of a research that examined four domains that affect students achievement, namely the strategies and teacher’s behavior in learning, planning and preparation done before learning, reflection on learning, and collegiality that supported teacher professionalism. This study aims at describing the strengths and weaknesses of teacher’s in Arabic learning process, and describing the need for teachers to increase professionalism. This study aims to describe the strengths and weaknesses of teachers in Arabic learning process, and describe the need for teachers to increase frofesionalism in teaching. The data was obtained by an instrument in form of a questionnaire of teacher’s self evaluation. Respondents consisted of Arabic teacher senior high school of the MAN 3 Rawasari, Jakarta. The instrument used has been validated. The result showed that most of the teachers carried out most of the components contained in the strategies and teaching behaviors and implemented teaching planning and preparation. In teaching planning and in learning process, however, teacher colleagues were still rarely involved for professional development. Reflection on the learning process and planning is rarely conducted jointly with colleagues. For further improvement of teacher learning, more intensive discussion with colleagues, principals, and supervisors are required. Besides, teachers can observe teaching process of other teachers, obtain feedback on learning not only from colleagues but also from principals and supervisors, and coaching done by the principal or learning expert.